Fluid needs for training, competition, and recovery in track-and-field athletes - Casa, D. J.; Cheuvront, S. N.; Galloway, S. D.; Shirreffs, S. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Seasonal environmental changes can create unique challenges for year-long training among track-and-field athletes. However, the competitive track-and-field season is held in the summer months of the northern hemisphere and major international track-and-field competitions, such as the World Championships and the Olympic Games culminate in the hottest months of the year. The 2019 IAAF Track-and-Field World Championships will take place in Qatar in the Middle East. The 2020 Summer Olympics will take place in Tokyo, Japan. It is quite likely that these events may set the records for the hottest Track-and-Field World Championships and Olympic Games in recorded history. Serious caution is often warranted for hot-weather Olympic track-and-field events (Nielsen, 1996) and the safe preparation and conduct of competitive hot-weather exercise is of great international interest (Racinais et al., 2015). Given the extreme heat in which training and competition are likely to take place in Qatar, Tokyo, and other summer sporting venues of the future, the risks associated with dehydration could be amplified more than in previous years. This review focuses on the risks of dehydration and potential consequences to performance in track-and-field events. We also discuss strategies for mitigating the risk of dehydration.